Improving Science Learning Outcomes Through the SETS (Science Environment Technology And Society) Approach - Ni Luh Gede Karang Widiastuti; I Putu Edy Purnawijaya (Indonesian Journal Of Educational Research and Review, 2021)
Science learning packaging still focuses on conventional learning. This causes students to feel bored in learning and have difficulty understanding the material taught by the teacher. This problem affects the students' low science learning outcomes. This study aims to analyze the significant differences in science learning outcomes for groups of students who are taught through the application of the SETS approach and students who are taught through conventional learning. This type of research is a quasi-experimental research design with nonequivalent control group design. The population and sample in this study were all students in grades IIIa and IIIb, totaling 61 people. The data collection technique in this research is a test. The technique used to analyze the data is using t-test statistical analysis. The results showed that there was a significant difference in science learning outcomes between the experimental and control groups as seen from the value of tcount = 5.862 > ttable = 2,000. Based on the results of the study, it can be concluded that the SETS approach has an effect on students' science learning outcomes. This research implies that the SETS approach can assist teachers in developing the learning process.